Family Characteristics That Suffer Stunting in the Work Area of The District Health Center Langkat - Nasution, Siti Saidah; Girsang, Bina Mellvia (Caring: Indonesian Journal of Nursing Science, 2019)
Stunting is malnutrition a long time and have an adverse impact on health status, growth and development of children. Signs and symptoms of stunting is child's posture is short i.e. the height is not appropriate with age. Malnutrition in children is related to the characteristics of the family as a place of growing and the care of the child. This research is descriptive quantitative research with the aim to analyze the characteristics of families with children who suffer from stunting. The study population 136 as much as with the total sample of 30 mothers who have children and toddlers with simple random sampling. Data collection using a questionnaire, consisting of demographic data, the role of family function and health status associated with stunting. Data analysis univariate. The results of the research showed that the. The importance of assessing the characteristics of the family in the treatment in children and infants.